Frequency And Type Of Refractive Errors Among The Teenage Groups Presenting In Eye OPD In Shaikh Zayed Hospital Lahore - Rahim, Sumaira; Abbas, Irum; Ahmed, Atif Mansoor; Arif, Zyiemah; Qudos , Abdul; Imdad, Tehmina (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the frequency and type of refractive errors in the teenage groups reporting in ophthalmology department of Shaikh Zayed Hospital Lahore, Pakistan. Methods: This descriptive study was conducted in the Shaikh Zayed Hospital, Lahore, Pakistan from 14-9-2023 to 14-02-24. Total 501 subjects of both genders with refractive errors were included in the study after fulfilling the inclusion criteria. . Participants were in the age group 11-19 years. Visual acuity was checked with Snellen chart. Subjective and objective refraction was performed. All participants underwent complete ophthalmic examination to rule out any ocular abnormality. Results: In the study 287 (57.3 %) participants were females and 214 (42.7%) were males. Median age of the participants was 16 years. Myopia was most prevalent refractive error with total of 339 (67.7%) followed by astigmatism having total 148 (29.5%). while hyperopia was seen in 14 (2.8%) participant of the study population. There were no gender related differences in distribution of refractive errors. Fewer cased were seen in age group 11 and 12 years. Almost 86% of the subject achieved visual acuity of 6/6 in both eyes after correction. Conclusion: myopia is a most prevalent form of ametropia in teenage groups. There is a need of creating awareness regarding its risk factors and life style modifications which can help in reducing burden of visual impairment